Dedi Mulyadi's Political Communication Strategy in The 2024 West Java Gubernatory Election: Analysis Through The Agenda Setting Approach - Ai Norma Yunita; Al Haura Millani; Anissa Rizqi Syafitri; Citra Dewi Agustin (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
Dedi Mulyadi's successful 2024 West Java Gubernatorial Election campaign integrated traditional Sundanese culture with digital media, a strategy analyzed through a descriptive qualitative methodology examining academic sources, online news, and social media. His consistent portrayal as a compassionate, humble, and approachable leader, amplified by positive content on YouTube, Facebook, and TikTok, was central to his political communication. Mulyadi deliberately utilized Sundanese cultural symbols to reinforce his political identity, while significant support from a coalition of political parties broadened his electoral reach. Through an effective agenda-setting strategy, he successfully framed crucial issues positively, thereby countering negative campaigns and offering valuable insights for future local political communication approaches that blend digital and cultural elements.